Following Fallis: A Literary Walk with "The Best Laid Plans" - Cerroni Lawlor, Jacqueline (Université d'Ottawa / University of Ottawa, 2012)
Lingering in the topic of literary engagement, this article follows a reader enthralled by words and the significant non-space where fiction and reality intersect. Using Terry Fallis’ political satire “The Best Laid Plans,” a physical map of the reading is followed as I amble through the Ottawa sites depicted in the novel. In this literary pilgrimage, reading is considered as a corporeal (re)action with a series of educative affects. Contrasting this experience with common in-school reading practices, this narrative encourages the honouring of the individualized relationship between reader and text as well as highlighting the pedagogical value of dallying in a work of fiction. Drawing on concepts of spatiality, I contemplate the notion of the home city as a familiar and yet capricious place, made more significant by a fantastic connection. Reading in significant spaces has a lasting, sprawling outcome whereby text, place and reader are all affected.
Keywords: education; reading; literary pilgrim